Orbital Apex Syndrome Following Herpes Zoster Ophthalmicus: A Case Report and Clinical Approach - Mehrdad Motamed Shariati; Farid Shekarchian; Ali Zolfaghari (Clinical Case Reports)
ABSTRACT Given the potential for rapid progression and significant morbidity, clinicians should maintain a high index of suspicion for OAS in patients with HZO who present with neurological symptoms such as ophthalmoplegia, ptosis, and sensory loss.